2021
DOI: 10.3390/genes12030456
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Regions Associated with Concentrations of Milk Fat, Protein, Urea and Efficiency of Crude Protein Utilization in Grazing Dairy Cows

Abstract: The objective of this study was to identify genomic regions associated with milk fat percentage (FP), crude protein percentage (CPP), urea concentration (MU) and efficiency of crude protein utilization (ECPU: ratio between crude protein yield in milk and dietary crude protein intake) using grazing, mixed-breed, dairy cows in New Zealand. Phenotypes from 634 Holstein Friesian, Jersey or crossbred cows were obtained from two herds at Massey University. A subset of 490 of these cows was genotyped using Bovine Ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…The largest three QTL intervals, on chromosomes 6, 11 and 14, all included well-known QTL associated with milk traits in dairy cattle [ 32 35 ]. The most significant QTL interval detected on chromosome 6, between 85,389,494 and 86,548,307 bp, overlaps with a QTL detected for MUN by Ariyarathne et al [ 13 ]. While the most significant variant in this QTL was an intergenic variant, the interval included the casein genes CSN1S1 , CSN1S2 , CSN2 and CSN3 , which are associated with milk production traits [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The largest three QTL intervals, on chromosomes 6, 11 and 14, all included well-known QTL associated with milk traits in dairy cattle [ 32 35 ]. The most significant QTL interval detected on chromosome 6, between 85,389,494 and 86,548,307 bp, overlaps with a QTL detected for MUN by Ariyarathne et al [ 13 ]. While the most significant variant in this QTL was an intergenic variant, the interval included the casein genes CSN1S1 , CSN1S2 , CSN2 and CSN3 , which are associated with milk production traits [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 64%
“…While the most significant variant in this QTL was an intergenic variant, the interval included the casein genes CSN1S1 , CSN1S2 , CSN2 and CSN3 , which are associated with milk production traits [ 33 , 34 ]. The most significant QTL interval on chromosome 11 overlapped with another QTL reported by Ariyarathne et al [ 13 ]. This interval was located between 100,851,568 and 104,180,090 bp, with a synonymous variant located in the GLT6D1 gene as the most significant variant.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…When the variant in PAEP was included as a fixed effect in the model, the only remaining significant variant was an intron in the vav guanine nucleotide exchange factor 2 ( VAV2 ) gene located at 104,765,599 bp with a p-value of 9.7 × 10 –7 . Ariyarathne et al [ 10 ] reported a QTL for MUN in the same region on chromosome 11. MUN and MBUN had a genetic correlation of 0.77 in the dataset used in the current study [ 5 ], hence QTL for MBUN and MUN were expected to overlap.…”
Section: Resultsmentioning
confidence: 99%
“…While the power of a GWAS for BUN may be limited due to the difficulties in obtaining a sufficient number of samples, MBUN may provide an alternative to detect quantitative trait loci (QTL) associated with BUN. While several GWAS have been published for milk urea nitrogen (MUN) [ 10 12 ], a trait that is highly related to BUN [ 5 , 13 ], to our knowledge, no GWAS has been published for either BUN or MBUN. Therefore, the objective of our study was to perform GWAS for BUN measured from blood samples and MBUN predicted from milk samples using spectroscopy, compare these two GWAS and detect QTL for both traits, and compare the detected QTL with previously reported QTL for MUN.…”
Section: Introductionmentioning
confidence: 99%